2014
DOI: 10.1007/s10974-014-9396-7
|View full text |Cite
|
Sign up to set email alerts
|

The disorders of the calcium release unit of skeletal muscles: what have we learned from mouse models?

Abstract: Calcium storage, release, and reuptake are essential for normal physiological function of muscle. Several human skeletal muscle disorders can arise from dysfunction in the control and coordination of these three critical processes. The release from the Sarcoplasmic Reticulum stores (SR) is handled by a multiprotein complex called Calcium Release Unit and composed of DiHydroPyridine Receptor or DHPR, Ryanodine Receptor or RYR, Calsequestrin or CASQ, junctin, Triadin, Junctophilin and Mitsugumin 29. Malignant hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…The heater organ is filled with SR membranous network surrounded by many mitochondria; continuous leak and reuptake of Ca 2+ by SERCA leads to heat generation [42–46]. The involvement Ca 2+ cycling in heat production is also observed in a pathological condition called “malignant hyperthermia (MH)”, caused by a mutation of the ryanodine receptor that results in uncontrolled Ca 2+ leak from the SR activating SERCA and heat production [47, 48]. Muscle-based Ca 2+ cycling in thermogenesis was suggested in cold acclimatized birds [4951].…”
Section: Sr Ca2+ Cycling Plays a Role In Muscle Thermogenesismentioning
confidence: 99%
“…The heater organ is filled with SR membranous network surrounded by many mitochondria; continuous leak and reuptake of Ca 2+ by SERCA leads to heat generation [42–46]. The involvement Ca 2+ cycling in heat production is also observed in a pathological condition called “malignant hyperthermia (MH)”, caused by a mutation of the ryanodine receptor that results in uncontrolled Ca 2+ leak from the SR activating SERCA and heat production [47, 48]. Muscle-based Ca 2+ cycling in thermogenesis was suggested in cold acclimatized birds [4951].…”
Section: Sr Ca2+ Cycling Plays a Role In Muscle Thermogenesismentioning
confidence: 99%
“…A fulminant MH syndrome is characterized by an uncontrolled increase in myoplasmic free calcium (Ca 2+ ) that leads to increased metabolic rate and subsequently results in hyperthermia and muscle rigidity 2‐4 . This energetic crisis can be triggered by volatile anesthetics, depolarizing muscle relaxants (eg, succinylcholine), intense exercise, and exposure to elevated environmental temperatures 5 . The prevalence in the human population of known MH‐causative mutations is 1:2750, 6 with variants in the ryanodine receptor 1 gene ( RYR1 ) being responsible for the majority of MH cases 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the phenotype affects predominantly fast muscles [extensor digitorum longus (EDL) muscle but not soleus]. The phenotypes of Casq1 −/− and Ryr1-mutant mice overlap strikingly (see Table 3; Canato et al, 2015), including increased mitochondrial damage and elevated ROS levels that can be ameliorated with antioxidant administration (Durham et al, 2008;Paolini et al, 2015). Of note, electron-dense aggregates ( presumed by the authors to be CASQ1) were observed by electron-microscopy analysis of Ryr1 I4895T/+ mice (Boncompagni et al, 2010), further highlighting the overlapping phenotypes of congenital myopathies.…”
Section: Recessive Ryr1 Modelsmentioning
confidence: 99%